Human Resource Development Through Knowledge Management System - Rahayuningtyas, Tri Esti; Widyatmoko, Widyatmoko; Mintorini, Ery; Chandriana, Tri Dian (Journal of Applied Intelligent System, 2023)
In the era of globalization, knowledge within the company has become something that is very decisive for the success of a company. Knowledge Management System (KMS) as a key element in knowledge management, is an application system used by organizations to manage tacit and explicit knowledge as a platform for communicating information. Employee Cooperative (Kopkar) PT. Gudang Garam Tbk is a cooperative engaged in savings and loans under the auspices of PT. Gudang Garam Tbk Kediri which has a very important role in improving the welfare of employees. The advancement of science and technology is a new challenge for the HR & General Division to process the knowledge assets owned by each employee. As a result of the very accelerating effect of globalization, the emphasis on the importance of the quality of human resources (HR) is one response in responding to these changes. This research method uses data collection methods, data analysis and software development. While analyzing the knowledge management process into a client/server oriented system using the SECI model. From the report, 80% of the discussions that are often shared are in the category of cooperative management issues, and 20% discuss articles about the role of technology and how to grow productivity in an organization.